2013
DOI: 10.11607/jomi.3001
|View full text |Cite
|
Sign up to set email alerts
|

Palatal Positioning of Implants in Severely Atrophic Edentulous Maxillae: Five-Year Cross-Sectional Retrospective Follow-up Study

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Therefore, reliable and accurate measuring tools are necessary to evaluate peri‐implant CBL. Furthermore, upon a vigilant evaluation of all the studies included in the present systematic review, it was observed that the time in situ varied significantly (1 to 22 years) between the included studies and that other related factors (such as soft tissue thickness, implant positioning, crestal or subcrestal placement, platform switching, crown‐to‐implant ratio, and presence of adjacent teeth) that have been associated with CBL remained unaddressed. However, splinting of short implants in particular has been recommended by some authors …”
Section: Discussionmentioning
confidence: 98%
“…Therefore, reliable and accurate measuring tools are necessary to evaluate peri‐implant CBL. Furthermore, upon a vigilant evaluation of all the studies included in the present systematic review, it was observed that the time in situ varied significantly (1 to 22 years) between the included studies and that other related factors (such as soft tissue thickness, implant positioning, crestal or subcrestal placement, platform switching, crown‐to‐implant ratio, and presence of adjacent teeth) that have been associated with CBL remained unaddressed. However, splinting of short implants in particular has been recommended by some authors …”
Section: Discussionmentioning
confidence: 98%
“…A total of 104 studies were excluded during the eligibility phase, with the main reason for exclusion being insufficient details on the prostheses or materials other than metal‐ceramic and all‐ceramic (Fig ). The screening for eligibility phase led to the inclusion of 23 articles with a mean follow‐up time of at least 1 year . Interassessor agreement during the eligibility screening II was “Good” (Kappa value: 0.87).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding framework fractures, metalacrylic CFIDPs experienced a cumulative 5-year complication rate of 3.0 to 4.9%, whereas for metal-ceramic CFIDPs, there was only 1 in 235 (0.43%) prostheses after a mean followup period of 5 years, and all-ceramic CFIDPs experienced no framework fracture at all. A possible explanation for the 35 Selection: Score = 4 * (a) Representation of the exposed cohort = 1 * (b) Selection of the exposed non cohort = 1 * 38 11/18 Oliva et al, 2012 40 9/18 Penarrocha-Oltra et al, 2014 41 12/18 Romanos et al, 2014 43 8/18 minimum incidence of all these mechanical complications in the included studies of this review, compared to previous studies on metal-acrylic CFIDPs, could be the advances in materials, screw mechanics, and interfaces, as well as dental technology, as most of the metal-acrylic CFIDPs studies were older than the ones studying metal-ceramic or all-ceramic prostheses. A systematic review 16 of the clinical success of both tooth-and implant-supported zirconia fixed dental prostheses identified four studies of CIFDPs.…”
Section: Results Of This Studymentioning
confidence: 99%
See 2 more Smart Citations